Difference in long-term clinical outcome after cardiac resynchronisation therapy between ischaemic and non-ischaemic aetiologies of heart failure. Issue 2 (24th July 2008) - Zhang, Q; Fung, J W-H; Chan, J Y-S; Yip, G; Lam, Y-Y; Liang, Y-J; Yu, C-M
Abstract : Objective: To examine the impact of heart failure (HF) aetiology on long-term outcome after cardiac resynchronisation therapy (CRT). Design: Prospective cohort study. Setting: University hospital. Patients: 119 patients (44% with ischaemic and 56% non-ischaemic aetiology) who underwent CRT. Interventions: Clinical follow-up for 39 (24) months. Main outcome measures: Cardiovascular mortality, HF and cardiovascular hospitalisation were compared by Kaplan-Meier curves between the two groups, followed by Cox regression analysis for prognostic predictor(s). Results: 41 (34%) patients died, in whom cardiovascular causes were identified in 32 (27%) patients. The ischaemic group had a higher cardiovascular mortality (log-rank χ 2 = 4.293, p = 0.038) and cardiovascular hospitalisation (log-rank χ 2 = 5.123, p = 0.024) when compared with the non-ischaemic group, though no difference was found in HF hospitalisation (log-rank χ 2 = 0.019, p = 0.892). At three months, left ventricular reverse remodelling occurred in 52% of the ischaemic group and 55% of the non-ischaemic group (χ 2 = 0.128, p = 0.720). By Cox regression analysis, ischaemic aetiology and absence of reverse remodelling at three months were independent predictors of cardiovascular mortality (HR = 2.698, p = 0.032; HR = 3.541, p = 0.030) and cardiovascular hospitalisation (HR = 1.905, p = 0.015; HR = 2.361, p = 0.004). Furthermore, these two factors had an incremental value in predicting cardiovascular mortality when compared with either alone (left ventricular reverse remodelling, log-rank χ 2 = 10.275 vs 6.311, p = 0.05; Ischaemic aetiology, log-rank χ 2 = 10.275 vs 4.293, p<0.05). Conclusion: Ischaemic aetiology of HF is an independent predictor of higher cardiovascular mortality and hospitalisation after CRT. This may implicate the progressive nature of coronary heart disease leading to a worse outcome despite similar short-term benefits of CRT.